Probabilistic seismic risk assessment of concrete bridge piers reinforced with different types of shape memory alloys. (1st May 2018) - Billah, A.H.M. Muntasir; Alam, M. Shahria
Highlights: Performance based seismic evaluation of Shape memory alloy reinforced concrete bridge pier. Comparative performance evaluation of different SMA-RC bridge pier. Probabilistic risk assessment of SMA-RC bridge pier. Seismic hazard assessment using crustal, inslab and interface events. Fe- based SMA (FeNCATB) provides improved seismic performance. Abstract: Shape memory alloy (SMA) has emerged as an alternative to conventional steel reinforcement for improving the seismic performance of bridges during an extreme earthquake. This paper presents the probabilistic seismic risk assessment of concrete bridge piers reinforced with different types of SMA (e.g. Ni-Ti, Cu-Al-Mn, and Fe-based) rebars. To achieve this objective, the bridge piers are designed following a performance-based approach. Ground motions with different probable earthquake hazard scenarios at the site of the bridge piers are considered. Probabilistic seismic demand models are generated using the response parameters obtained from incremental dynamic analysis. Considering maximum drift and residual drift as demand parameters, fragility curves are developed for five different SMA-RC bridge piers. Finally, seismic hazard curves are generated in order to compare the mean annual rate of exceedance of different damage states of different bridge piers. It is observed that all the bridge piers perform according to the design objective, and the performance of SMA-RC piers is significantly affected by the type of SMA used. The results show that all the SMA-RC piers have very low probability of collapse at maximum considered earthquake level. It is found that the bridge pier reinforced with FeNCATB-SMA (SMA-3) performed better as compared to the other SMA-RC piers.